Maternal body fluid composition in uncomplicated pregnancies and preeclampsia: a bioelectrical impedance analysis. (September 2016) - Staelens, Anneleen S.; Vonck, Sharona; Molenberghs, Geert; Malbrain, Manu L.N.G.; Gyselaers, Wilfried
Abstract: Objectives: Body fluid composition changes during the course of pregnancy and there is evidence to suggest that these changes are different in uncomplicated pregnancies compared to hypertensive pregnancies. The aim of this study was to evaluate the changes in maternal body fluid composition during the course of an uncomplicated pregnancy and to assess differences in uncomplicated pregnancies versus hypertensive pregnancies by using a bio-impedance analysis technique. Study design: Body fluid composition of each patient was assessed using a multiple frequency bioelectrical impedance analyser. Measurements were performed in 276 uncomplicated pregnancies, 34 patients with gestational hypertension, 35 with late onset preeclampsia and 11 with early onset preeclampsia. Statistical analysis was performed at nominal level α = 0.05. A longitudinal linear mixed model based analysis was performed for longitudinal evolutions, and ANOVA with a post-hoc Bonferroni was used to identify differences between groups. Results: Measurements showed that total body water (TBW), intracellular (ICW) and extracellular water (ECW) and ECW/ICW significantly increase during the course of pregnancy. Late onset preeclampsia is associated with a higher TBW and ECW as compared to uncomplicated pregnancies, the ECW/ICW ratio is higher in preeclamptic patients compared to uncomplicated pregnancies and gestational hypertension, and ICW is not different between groups. Conclusion: Body fluid composition changes differently during the course of uncomplicated pregnancies versus hypertensive pregnancies.